2022
DOI: 10.3389/fcvm.2022.969259
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent use of statins decreases major bleeding and intracerebral hemorrhage in non-valvular atrial fibrillation patients taking direct oral anticoagulants—A nationwide cohort study

Abstract: BackgroundStatins are frequently prescribed with direct oral anticoagulants (DOACs), and previous studies have raised concerns about the increased risk of intracerebral hemorrhage or other major bleeding in concurrent statins and DOACs use. The objective of this study is to evaluate the risk of major bleeding in non-valvular atrial fibrillation patients taking DOACs with or without statins.MethodsThis nationwide, retrospective cohort study used data from the Taiwan National Health Insurance Research Database, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Due to the possibility of drug-drug interactions that could impact bleeding risks, particularly in the setting of surgery, research has been conducted on the interaction between Statins and anticoagulants, including warfarin. While some evidence suggests that Statins may raise the risk of bleeding when combined with warfarin, other studies suggest that Statins may lower the risk of bleeding in people using DOACs 33 , 34 . The effects may differ based on the particular statin and anticoagulant used, as well as patient-specific factors, and the evidence is not totally consistent.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the possibility of drug-drug interactions that could impact bleeding risks, particularly in the setting of surgery, research has been conducted on the interaction between Statins and anticoagulants, including warfarin. While some evidence suggests that Statins may raise the risk of bleeding when combined with warfarin, other studies suggest that Statins may lower the risk of bleeding in people using DOACs 33 , 34 . The effects may differ based on the particular statin and anticoagulant used, as well as patient-specific factors, and the evidence is not totally consistent.…”
Section: Discussionmentioning
confidence: 99%
“…The reason may be because of the relatively low actual anticoagulation rate despite the high proportion of patients at high risk in our study. Some studies have indicated that amiodarone, statins, and antibiotics could potentially elevate the risk of bleeding when taken with OACs [31][32][33][34][35][36][37] . However, the limited usage of OAC in the study may cause doctors to overlook the potential bleeding risk caused by drug interactions.…”
Section: Assessment Of Appropriateness Of Ppismentioning
confidence: 99%
“…2 An increased risk of ICH associated with statins and low cholesterol levels is supported by other studies, 3,4 but these associations remain controversial. [5][6][7] Cerebral microbleeds (CMBs) are hypointense lesions on T2-weighted gradient-echo magnetic resonance imaging (MRI). They are considered to be an asymptomatic precursor of ICH, especially in patients with a high burden of CMBs, 8,9 while they are also associated with an increased risk for ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…2 An increased risk of ICH associated with statins and low cholesterol levels is supported by other studies, 3,4 but these associations remain controversial. 57…”
Section: Introductionmentioning
confidence: 99%